Development of PjBL E-Modules with a Deep Learning Approach for Problem Solving and Scientific Literacy - Endang Susilowati; Dasrieny Pratiwi; Friska Octavia Rossa; Arif Rahman Aththibby (FKIP - Universitas Riau, 2026)
The low scientific literacy and problem-solving skills of elementary school students indicate the need for innovative learning media that are meaningful, contextual, and appropriate to student characteristics. One alternative solution is the development of Project-Based Learning (PjBL)-based e-modules integrated with a deep learning approach. This study aims to develop interactive e-modules on the human respiratory system that can increase student learning engagement, reflective thinking, and in-depth understanding. The development model used is 4D (Define, Design, Develop, Disseminate). The Define stage is carried out by analyzing the curriculum and student needs. The Design stage produces an e-module design with a project structure that integrates critical thinking activities. The Develop stage involves validation by material experts (score 78/80), media (76/80), and language (75/80) with the category